Properties of Polymer Addition Ratio for Efflorescence Reduction in Permeable Blocks - Lee, Sang-Soo; Yoo, Byeong-Yong; Lee, Won-Gyu (International Journal of Engineering and Technology, 2018)
Background/Objectives: In Korea, rapid industrial development has changed the flow of rainwater, and flooding of rivers and depletion of groundwater have become problems.Methods/Statistical analysis: The permeable block was manufactured, and the existing permeable block has the disadvantage of efflorescence. The efflorescence affects not only strength but also product life. In order to prevent the efflorescence, the use of cement, which is the main cause of the efflorescence, was reduced and fly ash as an alternative to cement was used as an industrial byproduct. Polymers were used to increase strength and durability.Findings: The test items were density, water absorption, flexural strength, compressive strength, porosity, permeability coefficient, and efflorescence state.Â Density and water absorption decrease as the polymer addition rate increases. The flexural strength and compressive strength increase as the addition rate of polymer increases. Porosity and permeability coefficient decrease as the addition rate of polymer increases but satisfy the KS standard. When the amount of efflorescence was observed, it was confirmed that the amount of efflorescence decreased as the addition rate of polymer increased.Improvements/Applications: Future experiments predict that non-cemented permeable blocks will be produced and will not produce efflorescence completely.Â Â